Climate Change, Migration and Social Vulnerability in Nepal - Magar, Deepak Pun (BARUN Journal, 2026)
Climate change has become an everyday reality for many communities in Nepal, shaping livelihoods, mobility, and social wellbeing. This study examines the interconnections between climate change, migration, and social vulnerability, highlighting how environmental stress interacts with existing social inequalities. The study uses a thematic and comparative analytical framework to interpret. Drawing on entirely secondary data, the research adopts a conceptual and descriptive methodology, reviewing academic literature, government reports, and publications from national and international organizations covering the period from 1990 to 2025. The findings show that climate-induced hazards such as floods, droughts, landslides, and glacial melting increasingly disrupt rural livelihoods, prompting migration as a coping and adaptation strategy. However, migration also produces new forms of vulnerability, particularly for women, marginalized castes, and economically disadvantaged groups. The study argues that climate change in Nepal functions as a social as well as environmental challenge, reinforcing structural inequalities. It concludes that inclusive, migration-sensitive, and socially just adaptation strategies are essential for strengthening resilience in a changing climate.